Fractional weighted ZF equalizer: A novel approach for channel equalization in MIMO-OFDM system under impulse noise environment - Girija, S. P.; Rao, Rameshwar (Communications in Science and Technology, 2021)
Impulse noise is the major factor degrading the performance of the wireless system, imposing the need for the impulse noise mitigation strategy. Mainly, in the multiple-input multiple-output (MIMO) and orthogonal frequency-division multiplexing (OFDM) system contaminated with the impulse noise creates a major impact in the performance as the conventional zero-forcing (ZF) equalizer as there is no satisfactory results. Thus, the paper concentrates on the impulse noise mitigation strategy based on the fractional weighed zero-forcing (FWZF) equalizer, which is the integration of the fractional concept in the Zero-Forcing equalizer. The noise impacts in the MIMO-OFDM system are minimized and the performance is enhanced due to the usage of the fractional theory in the ZF equalizer as the equalization values of the previous instances are interpreted for the formulation of the effective equalization value in the current instance of the ZF equalizer. The performance of the methods is done based on the valuation metrics, Bit Error Rate (BER), Mean Square Error (MSE), and Symbol Error Rate (SER) with respect to the Signal-to-Noise Ratio (SNR) and dissimilar antenna array size. It is found that the proposed Fractional Weighed Zero-Forcing equalizer outperformed the existing methods with a minimal BER and SER of 0.063, and 0.1038 while analyzing the methods in the Rayleigh environment.